2018
DOI: 10.1038/s41598-018-33275-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic export by efflux pumps affects growth of neighboring bacteria

Abstract: Cell-cell interactions play an important role in bacterial antibiotic resistance. Here, we asked whether neighbor proximity is sufficient to generate single-cell variation in antibiotic resistance due to local differences in antibiotic concentrations. To test this, we focused on multidrug efflux pumps because recent studies have revealed that expression of pumps is heterogeneous across populations. Efflux pumps can export antibiotics, leading to elevated resistance relative to cells with low or no pump express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…This observation might be due to the active efflux pump that can be specific for ciprofloxacin as substrate or the relatively low MIC 0.1 values against ASST. This is in good agreement with the efflux-mediated resistance to fluoroquinolones in many bacterial populations [29,32]. Cephalothin showed a comparably high inoculum effect against ARST (Figure 5b).…”
Section: Discussionsupporting
confidence: 84%
“…This observation might be due to the active efflux pump that can be specific for ciprofloxacin as substrate or the relatively low MIC 0.1 values against ASST. This is in good agreement with the efflux-mediated resistance to fluoroquinolones in many bacterial populations [29,32]. Cephalothin showed a comparably high inoculum effect against ARST (Figure 5b).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the same experiment repeated with a strain of E . coli that expresses the non‐social AcrAB‐TolC export pump as a mechanism of antibiotic resistance (Wen et al ., ) revealed that MIC was independent of initial cell density (Fig. S1).…”
Section: Resultsmentioning
confidence: 87%
“…Two-dimensional configurations, ranging from microcolonies growing on agarose pads to microfluidic growth chambers, can be used to measure spatial dynamics of cell-to-cell interactions. Examples include quorum sensing [25] and the effect of efflux pumps on neighboring cells in the presence of antibiotics [26]. Segmenting and tracking cells in two dimensions are more challenging than for cells constrained within the mother machine.…”
Section: Introductionmentioning
confidence: 99%